VERBALIZATION OF THE BEHAVIORAL ASPECT OF THE LINGUO-PHILOSOPHICAL CATEGORY OF “RELATIONS” IN ITALIAN AND ENGLISH LANGUAGES - Irina A. Savvateeva (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article is dedicated to the issue of reflecting human relations in a behavioral aspect in different languages. It presents the results of a comparative analysis of the semantic organization of meanings of conceptually related lexical units that share a common Latin root and verbalize the category of RELATIONS in Italian and English. Based on a detailed analysis of the nouns atteggiamento in Italian and attitude in English, conducted with consideration of the linguocognitive and linguocultural contexts, the semantic similarities and differences of these lexemes are identified. Both units denote an evaluation (positive or negative) in relation to certain circumstances. However, the Italian word emphasizes the awareness of external actions, while the English word refers to a reaction more associated with internal emotions and mental states. The analyzed lexemes atteggiamento and attitude demonstrate a tendency towards the dominance of the behavioral component in the semantics of the category of RELATIONS due to the actualization of diachronic components in their lexical meanings. The prospects for the research lie in the application of a comprehensive comparative methodology for a deeper study on evoluting meanings of lexical units that explicate the semiotic and axiological aspects of the category of RELATIONS in Italian and English.